2021
DOI: 10.1007/s11926-021-00985-0
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus in Children and Young People

Abstract: Purpose of Review Juvenile-onset systemic lupus erythematosus ((j)SLE) is an autoimmune/inflammatory disease that results in significant damage and disability. When compared to patients with disease onset in adulthood, jSLE patients exhibit increased disease activity, damage and require more aggressive treatments. This manuscript summarises age-specific pathogenic mechanisms and underscores the need for age group–specific research, classification and treatment. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 138 publications
(192 reference statements)
4
78
0
16
Order By: Relevance
“…The current study showed that most cases of cSLE appeared after the pubertal period (>12 years of age). It might be explained by the hormonal effects on SLE patients after puberty has been also observed in most studies (5).…”
Section: Discussionmentioning
confidence: 64%
“…The current study showed that most cases of cSLE appeared after the pubertal period (>12 years of age). It might be explained by the hormonal effects on SLE patients after puberty has been also observed in most studies (5).…”
Section: Discussionmentioning
confidence: 64%
“…Childhood-onset lupus, unlike adult-onset, is more aggressive with high disease activity, greater use of immunosuppressants, and accumulated damage that causes greater morbidity and mortality [ 27 ]. Despite these important differences, there are no specific classification criteria for this population group, which is why, over time, the same criteria have been used as in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, later in disease, as a result of tissue damage and cell death, type 1 interferon expression may “derail” and perpetuate inflammation and damage [9] . This is likely of significant relevance, as pathological spontaneous and/or increased activation of the type 1 interferon pathway is associated with autoimmune/inflammatory conditions, such as SLE, that share some clinical aspects of COVID-19, including cytokine storm, tissue damage, thromboembolic events, end others [9] , [43] . Below, we discuss the involvement of particular immune mechanisms, in COVID-19, and how drug delivery systems, such as nanoformulation, may improve therapeutic options.…”
Section: Immunological Responses In Covid-19mentioning
confidence: 99%